REVIEW OF THE BOOK: NEW STRATEGIES IN A CHANGING WORLD - Bolaños Martínez, Jorge (Journal of the Spanish Institute for Strategic Studies, 2013)
IS REVIEW:This is a summary of a manual of strategic studies and security, Plaza yValdéz Editores, Madrid, 2013